The Effect of Chlorogenic Acid Content in Coffee Can Reduce Malondialdehyde (MDA) and Increase Testosterone Hormone Levels in DM Conditions - Eko Naning Sofyanita; Achmad Zulfa Juniarto; Ari Suwondo; Heri Nugroho (Gema Lingkungan Kesehatan, 2025)
Hyperglycemia is an uncontrolled condition of DM in the body, which causes a decrease in cell functions due to an increase in free radicals (ROS). This study explored the effects of Chlorogenic Acid found in coffee on mitigating MDA levels and augmenting testosterone in the context of Diabetes Mellitus (DM). Chlorogenic Acid, recognized for its substantial antioxidative properties, may ameliorate cellular impairments resulting from high glucose concentrations, consequently elevating Testosterone levels. The methodology employed was a Randomized Control Posttest Group Design involving 20 male Rattus norvegicus rats, aged 8-12 weeks, divided equally into four distinct groups. DM was simulated by administering 40mg/KgBB of streptozotocin and verifying the onset of Hyperglycemia through blood glucose evaluations three days post-administration. Following the confirmation of Hyperglycemia, a 14-day intervention with Robusta Coffee was initiated, with subsequent blood sampling on the fifteenth day to measure MDA and Testosterone concentrations. Results indicated that the groups KP, KP1, and KP2 exhibited notable variations in their responses when contrasted with KP, achieving statistical relevance Of ANOVA (p<0.05). However, no marked difference was observed in Testosterone levels between KP1 and KP2 (p>0.05). The investigation corroborated that Chlorogenic Acid in coffee plays a crucial role in reducing MDA and increasing testosterone hormone levels in DM conditions.